Pengaruh Rasio Padat/Cair dan Waktu Pengadukan pada Proses Ekstraksi Silika dari Palm Oil Fly Ash (POFA) - Fika Rahma Yuni; Lita Darmayanti; Dewi Fitria (Department of Environmental engineering, Faculty of Science and Technology, Islamic State University Sunan Ampel Surabaya, 2021)
Palm oil fly ash (POFA) is one of the solid wastes produced from burning palm kernel shells and coir as a steam generator for palm oil mills. POFA has a high silica content and might potentially to be used as an adsorbent. The removal of impurity metals and the separation of SiO2 by extraction process is a way to improve the performance of silica. The extraction process is influenced by several factors including the solid/liquid ratio and the stirring time. This study used a solid/liquid ratio of 1: 8, 1:10, 1:12 and a stirring time of 120; 150; 180; and 210 minutes. The results showed the highest mass of silica deposits was at a ratio of 1:12 and stirring time of 210 minutes with a mass of 18.35 grams or 73.4% of 25 grams of POFA with a silica content of 47.97% and a silica surface area 8.18 m2/g. Silica from each variation was tested on peat water. The highest removal efficiency of color, organic matter, and Fe were 80%, 46%, and 37% respectively by the extracted silica with a solid/liquid ratio 1:12 and stirring time 210 minutes.